1981
DOI: 10.1530/jrf.0.0630443
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of progesterone, 17 -hydroxyprogesterone and 20 -dihydroprogesterone in the plasma of mares during pregnancy and at parturition

Abstract: Plasma concentrations of progesterone and 17 alpha-hydroxyprogesterone were high in the 2nd and 3rd months of gestation, but 20 alpha-dihydroprogesterone increased from a level of 2 ng/ml, during the first 3 months, to 10-15 ng/ml during months 5-10, to reach 80-120 ng/ml during the last 30 days before foaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…However, most studies on steroid secretion examined a limited number analytes and most used immunoassays only. The results presented here confirm the presence and pattern of secretion of 17OH-progesterone in pregnant mares (van Niekerk et al 1973, Holtan et al 1975a, Seren et al 1981, which increases by week 7 with formation of the endometrial cups (Holtan et al 1975a, Seren et al 1981, reaching peak concentrations of around 4 ng/ml by week 8 returning to baseline concentrations after week 20. This is consistent with ovarian expression of 17a-hydroxylase/17,20-lyase cytochrome P450 (P450c17), the enzyme directly responsible for 17OH-progesterone and androgen synthesis (Conley & Bird 1997, Neto et al 2010.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However, most studies on steroid secretion examined a limited number analytes and most used immunoassays only. The results presented here confirm the presence and pattern of secretion of 17OH-progesterone in pregnant mares (van Niekerk et al 1973, Holtan et al 1975a, Seren et al 1981, which increases by week 7 with formation of the endometrial cups (Holtan et al 1975a, Seren et al 1981, reaching peak concentrations of around 4 ng/ml by week 8 returning to baseline concentrations after week 20. This is consistent with ovarian expression of 17a-hydroxylase/17,20-lyase cytochrome P450 (P450c17), the enzyme directly responsible for 17OH-progesterone and androgen synthesis (Conley & Bird 1997, Neto et al 2010.…”
Section: Discussionsupporting
confidence: 84%
“…A variety of techniques have been used to measure steroid concentrations in the pregnant mare (Short 1959, van Niekerk et al 1973, Smith 1974, Squires et al 1974a, Burns & Fleeger 1975, Ganjam et al 1975, Holtan et al 1975a, Seren et al 1981, Tsumagari et al 1991, Hoffmann et al 1996. Some investigators utilized assays validated in part by incorporating chromatography in sample preparation (van Niekerk et al 1973, Barnes et al 1975, Ganjam et al 1975, Holtan et al 1975a, Atkins et al 1976 to reduce the potential interference from cross-reacting steroids but the resolution of separation was often limited compared with more contemporary chromatographic methods.…”
Section: Introductionmentioning
confidence: 99%
“…As was shown for 20a-DHP7 this progestagen starts to increase in the fifth month of pregnancy to reach 80-120 ng/ml during the last 30 days before foaling (Seren et al 1981). Since ovariectomy on day 140 consistently resulted in maintenance of pregnancy (Holtan et al 1979), the placental or fetoplacental unit must be considered the main source of gestagens during the latter half of pregnancy.…”
Section: Discussionmentioning
confidence: 89%
“…Some of the earliest reports used chromatography to minimize distortions in steroid estimates due to cross-reaction between the immunoassays subsequently employed, but sampling was infrequent (Barnes et al 1975, Ganjam et al 1975, Holtan et al 1975a. A decrease in immunoreactive progesterone (Lovell et al 1975, Seren et al 1981 and DHP (Hamon et al 1991) concentrations was noted by those using daily sampling but without chromatography. Although not statistically significant, the data associated with more frequent sampling (followed by immunoassay without chromatography) indicated that concentrations may drop only during the last 12 (Pope et al 1987) or 28 h (Haluska & Currie 1988).…”
Section: Discussionmentioning
confidence: 96%